The use of fluid silicone gels in the prevention and treatment of hypertrophic scars: a systematic review and meta-analysis. Issue 3 (May 2022) - De Decker, Ignace; Hoeksema, Henk; Verbelen, Jozef; Vanlerberghe, Els; De Coninck, Petra; Speeckaert, Marijn M.; Blondeel, Phillip; Monstrey, Stan; Claes, Karel E.Y.
Abstract: Background: Silicone products, either as a sheet or in fluid form, are universally considered as the first line therapy in the prevention and treatment of hypertrophic scars and keloids. However, the study results have been questioned by different authors and there has never been a large systematic synopsis published on the efficacy of fluid silicone gels. This systematic review aims to elucidate the available evidence of the results obtained by fluid silicone gels and present a complete and comprehensive overview of the available literature as well as a meta-analysis of the pooled data. Methods: A systematic search for articles concerning the use of silicone gel in the treatment and prevention of scars was performed on 3 different databases (Pubmed, Embase and Cochrane library) according to the PRISMA statement. Only RCT's were included. Qualitative assessment was done by 2 separate reviewers using the Cochrane risk of bias (RoB 2) assessment tool. Revman 5.4.1 software was used for meta-analysis. Results: The search yielded 507 articles. Two articles were identified through other sources. After deduplication and removal of ineligible records, 340 records were screened on title and abstract. Full text screening was done for 23 articles and ultimately 18 articles were included. A meta-analysis comparing fluid silicone gel to no treatment or placebo gels was conducted. Conclusion: Studies on the effects of liquid silicone gels on hypertrophic scars are numerous and this systematic review shows that the use of liquid silicone gels is associated with both a prophylactic and a curative effect on scars. However, a considerable amount of the available 'high evidence' trials are at a high risk for bias and it is uncertain whether or not the effects of silicone gels are comparable to silicone sheets and if the additional components present in many silicone gels are partially responsible for their scar improving capacity. Highlights: Fluid silicone gels are available in many different formulations with a wide variety of properties. The majority of RCTs investigating the efficacy of silicone gels are at a moderate to high risk for bias. Fluid silicone gels have a positive prophylactic and curative effect on scars. Fluid silicone gels reduce the scarring incidence, improve pliability, pigmentation, height and scar quality in general. A few studies suggesting the comparability of fluid silicone and silicone sheets are available, but are potentially biased.